Origin and geological significance of ultra-low resistivity in Lower Paleozoic marine shale, South China - Yuguang Hou; Kunpeng Zhang; Sheng He; Weifeng Qin; Yan Xiao; Cheng Wang; Rui Yu (地质科技通报, 2021)
Combining with the data of logging resistivity and organic geochemistry, polarizability test and Laser Raman spectra were used to analysze the main controlling factors of ultra-low resistivity (logging resistivity as low as 10-1 Ω·m and below) in the high evolution marine shale of Lower Paleozoic, southern China.Moreover, its internal cause and geological significance were also discussed in this paper.Results showed:1) The abundance and maturity of organic matter (OM) are the main factors affecting the ultra-low logging resistivity.There is a good negative correlation between TOC, logging resistivity and measured resistivity.Increasing of maturity will lead to the decrease in the minimum TOC threshold required to achieve ultra-low resistivity, and the polarizability of shale also increases.2) Graphitized OM is the main "conductive mineral" that causes ultra-low resistivity in high thermal evolution shales.The RmcRo corresponding to the critical point at which the OM begins to graphitize is about 3.5%.Extremely low resistivity is an important indicator that the structure of shale organic matter changed significantly and evolved to graphite.3) Logging response of the ultra-low resistivity is likely to indicate that the quality of shale reservoir has suffered great damage, such as exhaustion of hydrocarbon generation capacity, severely reduction of OM pores and adsorption capacity, and abruptly decline of gas content.Therefore, delineating the range of extremely low resistivity shale and excluding the high-risk area of "OM graphitization" could play a great significance role in shale gas assessment and target selection in high evolution Lower Paleozoic shale.